Multimedia Interaktif Berbasis Augmented Reality untuk Meningkatkan Problem Solving Skills dan Literasi Digital Siswa - Damanik, Nindita; Fajari, Laksmi Evasufi Widi (Jurnal Didaktika Pendidikan Dasar, 2025)
The aim of this research is to develop interactive multimedia based on augmented reality to improve problem solving skills and digital literacy of elementary school students. The research method used is Research and Development (R&D) with the ADDIE model. The research sample consisted of 35 fifth grade students at SDN Batok Bali and SDN 1 Pakuncenwho were selected using a purposive sampling technique. The data collection techniques used in this research were tests and questionnaires. The research results show: (1) the analysis stage was carried out with media analysis, curriculum analysis and material analysis; (2) the design stage is carried out by designing prototypes and research instrumens; (3) the development stage is carried out by developing prototypes and research instrumens, validity and reliability of instrumens and improving prototypes; (4) the implementation stage is carried out through interactive multimedia trials based on augmented reality; (5) the evaluation stage is carried out by analyze problem solving skills and digital literacy data using N-gain scores and analysis of student response questionnaires which shows that the level of practicality of the product is categorized as very practical. The conclusion of this research is that interactive multimedia based on AR can improve problem solving skills and digital literacy of elementary school students.